Pengaruh Kelengkapan Produk dan Penetapan Harga terhadap Keputusan Pembelian Konsumen pada Nano Store di Kabupaten Bandung Selama Pandemi COVID-19 - Faris Zikrurrahman; Rizal Muhammad Naufal; Harmon Chaniago (International Journal Administration, Business & Organization, 2021)
This study aims to determine and analyze the effect of product completeness and pricing on consumer purchasing decisions at the Nano Store in Bandung District during the Covid-19 pandemic. This type of descriptive quantitative research, while the data used is primary data collected through questionnaires to 110 respondents and analyzed using multiple regression analysis. The results showed that there was a significant influence between product completeness and pricing on consumer purchasing decisions, this is evidenced by the R Square value of 0.608, which means that product completeness and pricing have an effect of 60.8% on purchasing decisions and the remaining is 39.2. % influenced by other variables outside the independent variables studied. In this research, it can also be seen that simultaneously product completeness and pricing have a positive and significant effect on consumer purchasing decisions, which means that the more complete the product provided and the better the pricing, the higher the level of purchasing decisions.